Long-term Outcomes of Bone Conduction Hearing Implants in Patients With Bilateral Microtia-atresia - Fan, Xinmiao (Otol Neurotol, 2019)
To evaluate the long-term outcomes of three different types of bone conduction hearing implants (BCHI)—BAHA, Ponto, and Bonebridge—in Mandarin-speaking patients with bilateral microtia-atresia. METHODS: This cohort study enrolled 59 patients affected by bilateral microtia-atresia, with an upper bone conduction threshold limit of 30 dB HL at frequencies of 0.5 to 4 kHz. All subjects underwent unilateral BCHI surgery, including 26 (18 males, 8 females, of mean age 8.7 ± 1.9 yr) implanted with BAHA devices; 10 (7 males, 3 females, of mean age 11.7 ± 2.8 yr) implanted with Ponto devices; and 23 (14 males, 9 females, of mean age 9.0 ± 1.8 yr) implanted with Bonebridge devices. The main outcome measures included long-term audiological benefits, patient satisfaction, and complications. Each subject acted as his or her own control. RESULTS: Two years after BCHI surgery, the mean hearing thresholds in the BAHA, Ponto, and Bonebridge groups had improved to 22.6 ± 1.6 dB HL, 21.6 ± 1.2 dB HL, and 22.5 ± 1.5 dB HL, respectively. The mean percentages of subjects in these three groups recognizing speech at 65 dB SPL under quiet conditions were 97.7 ± 4.2%, 96.3 ± 1.1%, and 94.4 ± 9.4%, respectively, whereas the mean percentages recognizing speech under noise conditions (signal:noise ratio +5) were 87.0 ± 1.8%, 89.3 ± 9.3%, and 85.3 ± 4.7%, respectively. Questionnaires revealed patients’ benefits and satisfaction with this surgery. Three (11.5%) of 26 patients in the BAHA group and 1 (10%) of 10 in the Ponto group experienced skin irritation, but all recovered after local treatment. Five (19.2%) patients in the BAHA group and two (20%) in the Ponto experienced abutment extrusion about 6 months postoperatively, with all achieving good results after revision surgery to replace the abutment. One (3.8%) patient in the BAHA group experienced local chronic inflammation and underwent surgery to replace the BAHA with a Bonebridge implant. One (4.3%) patient in the Bonebridge group developed a local infection 3 months postoperatively and underwent implant removal. CONCLUSIONS: All three BCHIs were well tolerated after long-term follow-up, and all improved audiometric thresholds and the intelligibility of speech in the presence of both quiet and noise. These implants should be considered valid and safe options for the functional rehabilitation of patients with bilateral microtia-atresia.